Field of study, qualification mismatch, and wages: Does sorting matter? - Francesco Berlingieri; Ulrich Zierahn (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Graduates from Science, Technology, Engineering, and Mathematics (STEM) are usually found to have higher wages and a lower risk of overqualification. However, it is unclear whether we can interpret the effect of STEM subjects on overqualification and wages in a causal way, since individuals choosing these subjects might differ systematically in unobserved characteristics, such as ability. Using data on German male graduates we show that unobserved heterogeneity indeed matters for differences in the risk of overqualification and wages when STEM graduates are compared to the Business & Law group, while it plays only a minor role for the difference between STEM graduates and the Social Sciences & Humanities group.
urn:nbn:de:bsz:180-madoc-372040
Keywords: I21; J24; J31; 330; qualification mismatch; wages; sorting; graduates; field of study